2006
DOI: 10.1074/jbc.m600924200
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain of Glycoprotein Ibβ Is Critical to Efficient Expression of Glycoprotein Ib-IX Complex in the Plasma Membrane

Abstract: Lack of expression of glycoprotein (GP)Ib Platelet glycoprotein (GP)2 Ib-IX-V complex mediates the initial tethering and rolling of platelets on von Willebrand factor (vWF) localized at the vascular injury site (1, 2). Upon ligation with the A1 domain of vWF, the GP Ib-IX-V complex transmits inward a signal that leads to activation of integrin ␣IIb␤3 and eventual platelet activation and aggregation (3, 4).Although the GP Ib-IX-V complex is widely considered to comprise GP Ib␣, GP Ib␤, GP IX, and GP V with a 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(87 citation statements)
references
References 42 publications
(28 reference statements)
5
82
0
Order By: Relevance
“…1-2 3 10 4 cells/mL). The supernatant containing biotinylated GPIb-IX was further analyzed by Western blot and flow cytometry largely as described previously, 30,33,34 or it was stored at 280°C for the force measurement.…”
Section: Expression Of Biotinylated Gpib-ix and Mutantsmentioning
confidence: 99%
“…1-2 3 10 4 cells/mL). The supernatant containing biotinylated GPIb-IX was further analyzed by Western blot and flow cytometry largely as described previously, 30,33,34 or it was stored at 280°C for the force measurement.…”
Section: Expression Of Biotinylated Gpib-ix and Mutantsmentioning
confidence: 99%
“…2, A and B). In contrast, previous reports have shown that transient expression of mutant GP Ib␤ and GP IX whose TMDs are replaced either by polyleucine (pL, ␤ pL and IX pL ) or polyleucine-alanine (pLA, ␤ pLA and IX pLA ) residues causes nonexpression of GP Ib␣ only in mutant GP Ib␤ cells instead of mutant GP IX cells (38). Therefore, it is possible that 1) the pL or pLA type of TMD may by itself interfere with the expression of GP Ib␤ and therein GP Ib␣, and/or 2) the Trf TMD in the swapped GP Ib␤ has an improved capability of forming stable bonds with the TMDs of GP Ib␣ and GP IX to maintain a relatively higher expression of GP Ib␣ on the cell surface.…”
Section: Volume 290 • Number 36 • September 4 2015mentioning
confidence: 55%
“…Our previous studies show that the TM domain of Ibb is critical for efficient expression of the GP Ib-IX complex in the plasma membrane, because replacing the TM with poly-Leu or poly-LeuAla diminished surface expression of the GP Ib-IX complex in the plasma membrane. 8 Further studies showed that TM domain associations of Iba, Ibb, and IX domain favorably position the membrane-proximal Cys residues for disulfide bond formation, and this supports the ab 2 configuration. 5,9 All these observations suggest that the TM domains of the GP Ib-IX complex are responsible for functionally important associations of the GP Ib-IX complex in membranes.…”
Section: Introductionmentioning
confidence: 82%